CHANGES OF ECOLOGICAL-GEOCHEMICAL STATE OF TOPSOIL AND RIVER SEDIMENTS IN VILNIUS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The changes of environmental quality were revealed according to temporal differences of additive contamination indices calculated for topsoil and sediments of N eris and V okė r ivers i n V ilnius. T opsoil contamination indices were calculated on the basis of Ag, Ba, Co, Cr, Cu, Mn, Mo, Ni, Pb, Sn, V and Zn contents for 2 different periods (1985 and 1996-2002) and their comparison was realised on 237.86 sq. km territory of the first sampling. The areas, where topsoil ecological-geochemical state has worsened have been determined. Part of them with unallowable topsoil pollution level indicates the quarters, where population health risk increase is possible. Monitoring is necessary there, also health protection measures. The tendency of improvement of ecologicalgeochemical state of river sediments is observed, but potential sources of secondary pollution in sediments can be hazardous for downstream segments.